Single-phase Boost-type Active Tracking AC-AC Voltage Regulator with an Improved Hybrid Control Technique - Felix Hımmelstoss; Faruk Yalçın (Düzce Üniversitesi Bilim ve Teknoloji Dergisi, 2022)
This paper presents a switch-mode single-phase boost-type AC-AC voltage regulator. The topology of the regulator needs only reduced numbers of components. Unlike the similar studies in the literature, a new hybrid control technique with a closed-loop PID controller and a novel developed feedforward controller is applied to the regulator that enhances the active tracking of the reference output voltage to obtain a higher quality of the sine-wave output voltage, when the input AC voltage is an ideal pure sine or including different harmonics levels. The proposed regulator with the proposed control technique is tested both by simulation and experimentally. The experimental set-up for the regulator is designed for 0.75 kW output power, 0-100 Vp input voltage (50 Hz), and 0-200 Vp output voltage. The results have shown that the proposed switch-mode boost type regulator is capable of obtaining the desired AC voltage with harmonics lower than 5% THD (total harmonic distortion) for different input/output parameters and different load conditions.